Towards An Inclusive Nursing Education of Multicultural Pedagogies and Frameworks in Indonesia: A Systematic Review - Kabak, Edison; Olivar, Jennifer Joy Ramelb; Tukayo, Isak Jurun Hans (Public Health and Safety International Journal, 2025)
The lack of a comprehensive and culturally-tailored nursing education model that integrates multiculturalism and inclusivity causes widened health disparities and poor quality of care. The objective is to synthesize and critically appraise an effective pedagogical strategy, and implementation frameworks of multicultural and inclusive nursing education. This study utilized a systematic review design. Literature searches were conducted in Google Scholar, Scopus, ResearchGate, and Mendeley. Inclusion criteria encompassed publications from 2019-2024 focusing on multicultural, inclusive nursing education and cultural competence in Indonesia. The Joanna Briggs Institute (JBI) critical appraisal tools were used to assess methodological quality. Data analysis involved thematic synthesis using NVivo software and JBI. The systematic review identified 16 studies, revealed that 6 studies (37.5%) were of high quality, 4 (25%) were moderate, and 6 (37.5%) were low. Thematic analysis in NVivo identified five key themes: Curriculum Integration (n=10 studies), Educator Competence (n=8), Active Learning Strategies (n=12), Implementation Barriers (n=7), and Assessment Tools (n=5). The findings identified core components, effective pedagogical strategies, and implementation frameworks for multicultural nursing education in Indonesia, and recommended an immediate adoption and empirical testing to validate its impact on cultural competence and healthcare equity.